Subjective age and risk of incident dementia: Evidence from the National Health and Aging Trends survey. (May 2018) - Stephan, Yannick; Sutin, Angelina R.; Luchetti, Martina; Terracciano, Antonio
Abstract: The present study examines the association between subjective age and risk of incident dementia in a large longitudinal sample of older adults. Participants were adults aged 65 years and older from the National Health and Aging Trends Study (NHATS). Subjective age, covariates, and cognitive status were assessed in 2011 and cognitive status was again assessed in 2012, 2013, 2014 and 2015. Incident dementia was determined based on answers from self and proxy respondents. The analyses included 4262 participants without dementia at baseline. Adjusting for demographic factors and baseline cognition, an older subjective age was related to higher likelihood of incident dementia. This association was partly accounted by depressive symptoms. Beyond the effect of chronological age, feeling older is associated with the risk of incident dementia.